A low temperature medium and high voltage aluminum electrolytic capacitor

By using technical means such as modified nanosilicon dioxide and low melting point co-solvents in aluminum electrolytic capacitors, the problem of degradation of electrical performance in traditional aluminum electrolytic capacitors in low temperature environments is solved, and normal operation and efficient operation are achieved at extremely low temperatures.

CN119786266AActive Publication Date: 2025-04-08SHENZHEN XINZHONGYUAN ELECTRONICS CO LTD

Patent Information

Application Number
CN202510293030.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-04-08
Estimated Expiration
2045-03-13

AI Technical Summary

Technical Problem

The electrical performance of traditional aluminum electrolytic capacitors has significantly decreased in low temperature environments, resulting in failure to work properly in extreme low temperature environments, and even failing, limiting their application range.

Method used

Modified nanosilica is used as flash voltage booster, and the esterification reaction of polyvinyl alcohol and allyl succinic anhydride is carried out through the esterification reaction of polyvinyl alcohol and allyl succinic anhydride, and the surface of the nanosilica is modified by using vinyl silane coupling agent to make it evenly disperse in the electrolyte, forming a "shielding effect" to reduce local electric field concentration. At the same time, a low melting point co-solvent and high solubility conductive ion system are introduced to improve the conductivity and stability of the electrolyte.

Benefits of technology

It significantly improves the electrical performance of aluminum electrolytic capacitors in low temperature environments, ensures that the capacitor can work normally at extremely low temperatures, extends its service life, and improves its reliability in extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of aluminum electrolytic capacitors, and specifically discloses a low-temperature, medium- and high-voltage aluminum electrolytic capacitor. Among them, the electrolyte of the low-temperature, medium- and high-voltage aluminum electrolytic capacitor includes the following raw materials: a main solvent, a low-melting point co-solvent, a main solute, an auxiliary solute, a flash voltage enhancer, a hydrogen remover, and a waterproofing auxiliary agent. Among them, the flash voltage enhancer is modified nano-silica. The present invention uses a vinyl silane coupling agent to modify the surface of nano-silica, and then esterifies polyvinyl alcohol and allyl succinic anhydride to form allyl succinic anhydride-grafted polyvinyl alcohol, and effectively combines it with silanized nano-silica, so that the nano-silica particles can be evenly dispersed in the electrolyte to increase the flash voltage of the electrolyte, and by introducing a low-melting point co-solvent, the melting point of the electrolyte system can be effectively reduced, so that the capacitor can maintain low viscosity and good electrical properties in a low-temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum electrolytic capacitors, and specifically discloses a low-temperature, medium- and high-voltage aluminum electrolytic capacitor. Background Art

[0002] With the rapid development of modern industry, especially in aerospace, military equipment, polar expedition and other extreme environments, the application demand is increasing, and the performance requirements of electronic components are getting higher and higher. As an important electronic component, aluminum electrolytic capacitors are widely used in power filtering, coupling, bypass and other circuits because of their advantages such as large capacity, small size and low cost. However, the performance of traditional aluminum electrolytic capacitors in extreme temperature environments is not satisfactory, especially in low temperature environments (below -40°C), its electrical characteristics will drop significantly, making it difficult to meet actual use requirements.

[0003] In the production of aluminum electrolytic capacitors, the role of the working electrolyte is to repair defects on the anodized film at any time and maintain the performance and life of the capacitor. Traditional aluminum electrolytic capacitors usually use ordinary electrolytes and anode foils, and exhibit good electrical properties at room temperature. However, when the ambient temperature drops below -40°C, the viscosity of the electrolyte will increase significantly, causing its electrical performance to drop sharply, which not only affects the capacity and equivalent series resistance (ESR) of the capacitor, but may also cause the capacitor to fail to work properly or even fail in low temperature environments, thus severely limiting the application of aluminum electrolytic capacitors in extreme low temperature environments. Summary of the invention

[0004] In order to improve the electrical performance of aluminum electrolytic capacitors in low temperature environments and ensure the normal operation of the capacitors, the present application provides a low-temperature medium- and high-voltage aluminum electrolytic capacitor.

[0005] In the first aspect, the present application provides a low-temperature medium- and high-voltage aluminum electrolytic capacitor, which adopts the following technical solution: A low-temperature medium- and high-voltage aluminum electrolytic capacitor, comprising an electrolyte, an anode foil, a cathode foil, a lead terminal and a plastic-sealed shell; Wherein, the electrolyte comprises the following raw materials in parts by weight: 40-50 parts of main solvent, 20-30 parts of low melting point co-solvent, 15-25 parts of main solute, 5-15 parts of auxiliary solute, 5-9 parts of flash voltage enhancer, 0.7-1.3 parts of hydrogen remover, 1.2-1.8 parts of waterproofing auxiliary agent; The flash voltage enhancer is modified nano-silica, and the raw materials for preparing the modified nano-silica include polyvinyl alcohol, allyl succinic anhydride, vinyl silane coupling agent and nano-silica. The weight ratio of the polyvinyl alcohol, allyl succinic anhydride, vinyl silane coupling agent and nano-silica is (0.6-0.8): (0.3-0.5): (0.13-0.15): 1.

[0006] By adopting the above technical solution, the flash voltage enhancer uses nano-silica as the matrix, and introduces reactive double bonds through esterification reaction between polyvinyl alcohol and allyl succinic anhydride, providing active sites for subsequent grafting reactions. In addition, the surface of nano-silica is modified by a vinyl silane coupling agent, and double bonds are introduced on the surface of nano-silica. Vinyl and double bonds of allyl succinic anhydride undergo grafting reaction, and at the same time, its siloxane group (Si-O) undergoes condensation reaction with hydroxyl groups (-OH) on the surface of nano-silica, effectively combining nano-silica with the polyvinyl alcohol matrix, so that nano-silica particles can be evenly dispersed in the electrolyte, forming a "shielding effect" and reducing local electric field concentration in the electrolyte. Local electric field concentration is one of the main reasons for electrolyte breakdown. The presence of modified nano-silica can evenly distribute the electric field and reduce the formation of local high electric field areas, thereby increasing the flash voltage of the electrolyte and reducing the leakage current of the capacitor. In addition, the main solvent provides the basic solubility and conductivity of the electrolyte. By introducing a low-melting-point co-solvent, the melting point of the electrolyte system can be effectively lowered, allowing the capacitor to maintain low viscosity and good electrical properties in a low-temperature environment. The main solute and auxiliary solute provide conductive ions, and the solute system has a high solubility in the solvent system, which improves the conductivity of the electrolyte in a low-temperature environment and ensures the efficient operation of the capacitor.

[0007] Preferably, the preparation method of the modified nano-silicon dioxide is: (1) Dissolve polyvinyl alcohol in deionized water, add allyl succinic anhydride and benzoyl peroxide at 60-70°C, stir and react for 2-3 hours, add acetone after the reaction is completed to precipitate, wash and dry to obtain allyl succinic anhydride grafted polyvinyl alcohol; (2) dissolving the vinyl silane coupling agent in 95% ethanol to form a silane hydrolyzate, adding nano-silica to the silane hydrolyzate, and ultrasonically oscillating for 1-2 hours to obtain silanized nano-silica; (3) Add silanized nano-silica to deionized water, ultrasonically disperse for 30-40 minutes, add allyl succinic anhydride grafted polyvinyl alcohol, continue ultrasonically dispersing for 1-2 hours, add a mixture of benzoyl peroxide and sulfuric acid, mix evenly, stir to react for 3-4 hours, and dry to obtain modified nano-silica.

[0008] By adopting the above technical solution, the vinyl silane coupling agent undergoes a condensation reaction with the hydroxyl groups on the surface of the nano-silicon dioxide through its siloxane group to form a chemical bond, thereby forming an organic modification layer on the surface of the nano-silicon dioxide. The allyl succinic anhydride grafted polyvinyl alcohol undergoes a grafting reaction with the vinyl groups on the surface of the silanized nano-silicon dioxide through its double bond to form a stable chemical bond. The surface modification and grafting reaction of the nano-silicon dioxide improves its compatibility with the electrolyte, reduces the agglomeration of the nano-silicon dioxide particles, and thus improves the overall stability of the electrolyte.

[0009] Preferably, the vinyl silane coupling agent is at least one of vinyl trimethoxy silane, vinyl triethoxy silane and vinyl triisopropoxy silane.

[0010] By adopting the above technical solution, the vinyl silane coupling agent contains vinyl and siloxane groups, which can undergo condensation reaction with the hydroxyl groups on the surface of nano-silicon dioxide, and the vinyl groups can undergo grafting reaction with the double bonds on polyvinyl alcohol.

[0011] Preferably, the main solvent is ethylene glycol monomethyl ether.

[0012] Preferably, the low melting point co-solvent is prepared by compounding acetonitrile and dibutyl carbonate, and the weight ratio of acetonitrile to dibutyl carbonate is 1:(0.5-0.9).

[0013] By adopting the above technical scheme, the mixed solvent system contains ether bonds and has lower liquid viscosity and melting point. In addition, dibutyl carbonate has a low melting point and moderate viscosity. By adding acetonitrile and dibutyl carbonate to ethylene glycol monomethyl ether solvent to form a low melting point co-solvent, the melting point of the mixed solvent can be further lowered, and the crystallization of the electrolyte in a low temperature environment can be reduced, so that the electrolyte has a higher conductivity, which is beneficial to improving the low temperature performance of the electrolyte, expanding the reliable operating temperature range of the capacitor, and obtaining a capacitor with excellent working performance in an extreme temperature environment.

[0014] Preferably, the main solute is at least one of ammonium hydrogen phosphate, ammonium sebacate and ammonium azelate; and the auxiliary solute is spirobispyrrolidine quaternary ammonium tetrafluoroborate.

[0015] By adopting the above technical scheme, the cation of the tetrafluoroborate spirobispyrrolidine quaternary ammonium salt is composed of two spiro rings, presenting a symmetrical "8" shape, and has higher solubility in the above mixed solvent system. In addition, its steric hindrance is small, and it is easier to adsorb and desorb ions during the charging and discharging process, so the ion mobility is higher, so that the electrolyte has higher conductivity and more stable electrochemical properties.

[0016] Preferably, the hydrogen remover is at least one of p-nitrophenol, p-nitrobenzyl alcohol, m-nitroacetophenone and o-nitroanisole.

[0017] Preferably, the water-proofing auxiliary agent is at least one of phosphoric acid, hypophosphorous acid, mannitol, polypropylene alcohol, adipic acid diamide, and sorbitol.

[0018] By adopting the above technical solution, the dehydrogenating agent contains strong electron-attracting groups such as nitro (-NO2), which can significantly increase the electronegativity of the molecule, thereby inhibiting the precipitation of hydrogen, improving the stability of the electrolyte, and ensuring the sealing and safety of the capacitor. The main function of the water-proofing agent is to prevent the water in the electrolyte from hydrating with the aluminum electrode, thereby avoiding corrosion of the aluminum and decomposition of the electrolyte.

[0019] Preferably, the preparation method of the electrolyte is: Heat the main solvent to 70-80°C, add the auxiliary solvent thereto, mix well and heat to 130-140°C, add the main solute and the auxiliary solute, keep warm and stir for 30-40 minutes, then cool to 110-120°C, add the flash voltage enhancer and the waterproofing auxiliary agent, keep warm and stir for 30-40 minutes, cool to 100-105°C, finally add the dehydrogenating agent, keep warm and stir for 30-40 minutes, and naturally cool to room temperature to obtain the electrolyte.

[0020] By adopting the above technical solution, the electrolyte prepared by the above method has high conductivity, wide electrochemical window, high conductive ion concentration and good stability at low temperature.

[0021] Preferably, the anode foil and the cathode foil are parallel to each other and are inserted into the plastic-sealed shell. The anode foil and the cathode foil are led out through lead terminals, and the electrolyte is stored in the plastic-sealed shell.

[0022] Preferably, the aluminum purity of the anode foil is above 99.99%; the aluminum purity of the cathode foil is above 99.6%; the plastic package shell is made of polytetrafluoroethylene material, and the temperature resistance range of the plastic package shell is -60°C to +150°C; the lead terminal is made of silver-plated copper alloy.

[0023] By adopting the above technical solutions, the dense oxide film formed on the surface of high-purity aluminum anode foil effectively improves the insulation performance and energy storage capacity of the capacitor; the plastic-sealed shell made of cold-resistant polytetrafluoroethylene ensures the overall sealing of the capacitor, reduces the entry of moisture and other impurities into the interior, and extends the service life of the capacitor; the use of silver-plated copper alloy leads enhances the welding performance, reduces the contact resistance, and further improves the reliability and durability of the capacitor.

[0024] This application has the following beneficial effects: In this application, the flash voltage enhancer uses nano-silica as a matrix, and introduces reactive double bonds through esterification reaction between polyvinyl alcohol and allyl succinic anhydride to provide active sites for subsequent grafting reactions. In addition, the surface of nano-silica is modified by a vinyl silane coupling agent, and double bonds are introduced on the surface of nano-silica. Vinyl and double bonds of allyl succinic anhydride undergo grafting reaction, and at the same time, its siloxane group (Si-O) undergoes condensation reaction with hydroxyl groups (-OH) on the surface of nano-silica, effectively combining nano-silica with the polyvinyl alcohol matrix, so that nano-silica particles can be evenly dispersed in the electrolyte, forming a "shielding effect" to reduce local electric field concentration in the electrolyte. Local electric field concentration is one of the main reasons for electrolyte breakdown. The presence of modified nano-silica can evenly distribute the electric field and reduce the formation of local high electric field areas, thereby increasing the flash voltage of the electrolyte. In addition, the main solvent provides the basic solubility and conductivity of the electrolyte. By introducing a low-melting-point co-solvent, the melting point of the electrolyte system can be effectively lowered, allowing the capacitor to maintain low viscosity and good electrical properties in a low-temperature environment. The main solute and auxiliary solute provide conductive ions, and the solute system has a high solubility in the solvent system, which improves the conductivity of the electrolyte in a low-temperature environment and ensures the efficient operation of the capacitor. DETAILED DESCRIPTION

[0025] The present application is further described in detail below with reference to the embodiments.

[0026] Preparation Example 1 Preparation of modified nano-silica: (1) Dissolve 30 g of polyvinyl alcohol in 100 mL of deionized water, add 15 g of allyl succinic anhydride and 2 g of benzoyl peroxide at 60 ° C, stir and react for 2 h, add acetone after the reaction is completed to precipitate, wash and dry to obtain allyl succinic anhydride grafted polyvinyl alcohol; (2) Dissolve 6.4 g of vinyltrimethoxysilane in 95% ethanol to form a silane hydrolyzate, add 50 g of nano-silica to the silane hydrolyzate, and ultrasonically vibrate for 1 h to obtain silanized nano-silica; (3) Add silanized nano-silica to 100 mL of deionized water, and disperse it ultrasonically for 30 min. Add allyl succinic anhydride grafted polyvinyl alcohol, and continue to disperse it ultrasonically for 1 h. Add a mixture of benzoyl peroxide and sulfuric acid and mix well. Stir and react for 3 h. After drying, the modified nano-silica is obtained.

[0027] Preparation Example 2 Preparation of modified nano-silica: (1) Dissolve 49 g of polyvinyl alcohol in 100 mL of deionized water, add 28 g of allyl succinic anhydride and 3 g of benzoyl peroxide at 65 °C, stir and react for 3 h, add acetone after the reaction is complete to precipitate, wash and dry to obtain allyl succinic anhydride grafted polyvinyl alcohol; (2) dissolving 9.8 g of vinyl triethoxysilane in 95% ethanol to form a silane hydrolyzate, adding 70 g of nano-silica to the silane hydrolyzate, and ultrasonically vibrating for 2 h to obtain silanized nano-silica; (3) Add silanized nano-silica to 120 mL of deionized water, and disperse it ultrasonically for 35 min. Add allyl succinic anhydride grafted polyvinyl alcohol, and continue to disperse it ultrasonically for 2 h. Add a mixture of benzoyl peroxide and sulfuric acid and mix well. Stir and react for 3.5 h. After drying, obtain modified nano-silica.

[0028] Preparation Example 3 Preparation of modified nano-silica: (1) Dissolve 72 g of polyvinyl alcohol in 100 mL of deionized water, add 45 g of allyl succinic anhydride and 4 g of benzoyl peroxide at 70 °C, stir and react for 3 h, add acetone after the reaction is complete to precipitate, wash and dry to obtain allyl succinic anhydride grafted polyvinyl alcohol; (2) Dissolve 13.5 g of vinyl triisopropoxysilane in 95% ethanol to form a silane hydrolyzate, add 90 g of nano-silica to the silane hydrolyzate, and oscillate ultrasonically for 2 h to obtain silanized nano-silica; (3) Add silanized nano-silica to 150 mL of deionized water, and disperse it ultrasonically for 40 min. Add allyl succinic anhydride grafted polyvinyl alcohol, and continue to disperse it ultrasonically for 2 h. Add a mixture of benzoyl peroxide and sulfuric acid and mix well. Stir and react for 4 h. After drying, obtain modified nano-silica.

[0029] Example 1 A low-temperature medium- and high-voltage aluminum electrolytic capacitor, comprising an electrolyte, an anode foil, a cathode foil, a lead terminal and a plastic-sealed shell; Among them, the electrolyte raw materials include: 400g ethylene glycol monomethyl ether, 130g acetonitrile, 70g dibutyl carbonate, 150g ammonium sebacate, 50g tetrafluoroborate spirobispyrrolidine quaternary ammonium salt, 50g flash voltage enhancer (modified nano-silica prepared in Preparation Example 1), 7g p-nitrophenol, 6g hypophosphorous acid and 6g phosphoric acid.

[0030] The preparation method of the electrolyte comprises the following steps: Ethylene glycol monomethyl ether is heated to 70°C, acetonitrile and dibutyl carbonate are added thereto, the mixture is mixed and heated to 130°C, ammonium sebacate and spirobispyrrolidine quaternary ammonium salt of tetrafluoroborate are added, the mixture is kept warm and stirred for 30 minutes, then the temperature is lowered to 110°C, modified nano-silica, hypophosphorous acid and phosphoric acid are added, the mixture is kept warm and stirred for 30 minutes, the temperature is lowered to 100°C, and finally p-nitrophenol is added, the mixture is kept warm and stirred for 30 minutes, and the mixture is naturally cooled to room temperature to obtain an electrolyte.

[0031] Example 2 A low-temperature medium- and high-voltage aluminum electrolytic capacitor, comprising an electrolyte, an anode foil, a cathode foil, a lead terminal and a plastic-sealed shell; Among them, the electrolyte raw materials include: 450g of ethylene glycol monomethyl ether, 150g of acetonitrile, 100g of dibutyl carbonate, 200g of ammonium hydrogen phosphate, 100g of tetrafluoroborate spirocyclic bipyrrolidine quaternary ammonium salt, 70g of flash voltage enhancer (modified nano-silica prepared in Preparation Example 2), 10g of p-nitrobenzyl alcohol, 7g of mannitol and 8g of polypropylene alcohol.

[0032] The preparation method of the electrolyte comprises the following steps: Ethylene glycol monomethyl ether is heated to 75°C, acetonitrile and dibutyl carbonate are added thereto, the mixture is mixed and heated to 135°C, ammonium hydrogen phosphate and tetrafluoroborate spirobispyrrolidine quaternary ammonium salt are added, the mixture is kept warm and stirred for 35 minutes, the temperature is then lowered to 115°C, modified nano-silica, mannitol and polypropylene alcohol are added, the mixture is kept warm and stirred for 35 minutes, the temperature is lowered to 103°C, and p-nitrobenzyl alcohol is finally added, the mixture is kept warm and stirred for 35 minutes, and the mixture is naturally cooled to room temperature to obtain an electrolyte.

[0033] Example 3 A low-temperature medium- and high-voltage aluminum electrolytic capacitor, comprising an electrolyte, an anode foil, a cathode foil, a lead terminal and a plastic-sealed shell; Among them, the electrolyte raw materials include: 500g ethylene glycol monomethyl ether, 160g acetonitrile, 140g dibutyl carbonate, 250g ammonium azelaic acid, 150g tetrafluoroborate spirocyclic bispyrrolidine quaternary ammonium salt, 90g flash voltage enhancer (modified nano-silica prepared in Preparation Example 3), 13g m-nitroacetophenone, 9g adipic acid diamide and 9g sorbitol.

[0034] The preparation method of the electrolyte comprises the following steps: Ethylene glycol monomethyl ether is heated to 80°C, acetonitrile and dibutyl carbonate are added thereto, the mixture is mixed and heated to 140°C, ammonium azelaic acid and spirobispyrrolidine quaternary ammonium salt of tetrafluoroborate are added, the mixture is kept warm and stirred for 40 minutes, then the temperature is lowered to 120°C, modified nano-silica, adipic acid diamide and sorbitol are added, the mixture is kept warm and stirred for 40 minutes, the temperature is lowered to 105°C, and finally m-nitroacetophenone is added, the mixture is kept warm and stirred for 40 minutes, and the mixture is naturally cooled to room temperature to obtain an electrolyte.

[0035] Comparative Example 1 A low-temperature medium- and high-voltage aluminum electrolytic capacitor is different from Example 2 in that an equal amount of manganese dioxide is used in the electrolyte raw material to replace the modified nano silicon dioxide in the flash voltage enhancer.

[0036] Comparative Example 2 A low-temperature medium- and high-voltage aluminum electrolytic capacitor is different from Example 2 in that an equal amount of polyvinyl alcohol is used in the electrolyte raw material to replace the modified nano-silicon dioxide in the flash voltage enhancer.

[0037] Comparative Example 3 A low-temperature medium- and high-voltage aluminum electrolytic capacitor, which differs from Example 2 in that nano-silicon dioxide is directly added to the electrolyte raw material as a flash voltage enhancer.

[0038] Comparative Example 4 A low-temperature medium- and high-voltage aluminum electrolytic capacitor is different from Example 2 in that no flash voltage enhancer is added to the electrolyte raw material, that is, no modified nano-silicon dioxide is added.

[0039] Comparative Example 5 A low-temperature medium- and high-voltage aluminum electrolytic capacitor, which differs from Example 2 in that tetrafluoroborate spirocyclic bipyrrolidine quaternary ammonium salt is not added to the electrolyte raw material.

[0040] Comparative Example 6 A low-temperature medium- and high-voltage aluminum electrolytic capacitor is different from Example 2 in that acetonitrile is added alone as a low-melting-point co-solvent in the electrolyte raw material, that is, the electrolyte raw material in this comparative example includes: 450g of ethylene glycol monomethyl ether, 250g of acetonitrile, 200g of ammonium hydrogen phosphate, 100g of tetrafluoroborate spirocyclic bispyrrolidine quaternary ammonium salt, 70g of flash voltage enhancer (modified nano-silica prepared in Preparation Example 2), 10g of p-nitrobenzyl alcohol, 7g of mannitol and 8g of polypropylene alcohol.

[0041] The preparation method of the electrolyte comprises the following steps: Ethylene glycol monomethyl ether is heated to 75°C, acetonitrile is added thereto, the mixture is mixed and heated to 135°C, ammonium hydrogen phosphate and tetrafluoroborate spirobispyrrolidine quaternary ammonium salt are added, the mixture is stirred for 35 minutes, the temperature is then lowered to 115°C, modified nano-silica, mannitol and polypropylene alcohol are added, the mixture is stirred for 35 minutes, the temperature is lowered to 103°C, p-nitrobenzyl alcohol is added, the mixture is stirred for 35 minutes, the mixture is naturally cooled to room temperature, and an electrolyte is obtained.

[0042] The aluminum electrolytic capacitors prepared in Examples 1-3 and Comparative Examples 1-6 were used as samples for low temperature performance tests. The capacitance, equivalent series resistance (ESR), leakage current performance, and impedance of the capacitors were tested at room temperature 25°C or low temperature -45°C. The test results are shown in Table 1 below.

[0043] Table 1

[0044] According to the data in Example 2, Comparative Example 1 and Table 1, it can be seen that the invention in this application uses modified silicon dioxide as a flash voltage enhancer, which can not only enhance the dielectric strength of the electrolyte, effectively increase the flash voltage threshold, and reduce the breakdown risk in the electrochemical system, but also reduce viscosity and increase electrolyte fluidity in a low temperature environment. Although manganese dioxide has a higher dielectric constant, it can effectively increase the flash voltage threshold and reduce the breakdown risk in the electrochemical system, but it may increase the viscosity of the electrolyte in a low temperature environment, hinder ion migration, and reduce the overall conductivity.

[0045] According to the data in Example 2, Comparative Examples 2-3 and Table 1, it can be seen that the use of polyvinyl alcohol alone as a flash voltage booster in the electrolyte may increase the viscosity of the electrolyte and cause a decrease in conductivity. In addition, the direct use of nano-silicon dioxide as a flash voltage booster is prone to precipitation or aggregation in the electrolyte, resulting in unstable electrolyte performance, which seriously limits its application in harsh environments. In the present application, modified nano-silicon dioxide is used as a flash voltage booster in the electrolyte to increase the fluidity of the electrolyte, and the nano-silicon dioxide modified by polyvinyl alcohol, allyl succinic anhydride, and vinyl silane coupling agent can be evenly dispersed in the electrolyte, significantly improving the precipitation or aggregation phenomenon to maintain the stability of the electrolyte, keep the viscosity of the electrolyte at a low level, and make ion conduction smoother. ‌ According to the data in Example 2, Comparative Example 4 and Table 1, it can be seen that without adding a flash voltage enhancer, various performances are poor. When working at low temperatures, the viscosity of the electrolyte increases, resulting in reduced conductivity and significantly reduced electrical properties, making it difficult to meet actual use requirements. However, the present invention uses modified silicon dioxide as a flash voltage enhancer, which significantly reduces the viscosity of the electrolyte and improves the ion conduction efficiency. Even in a low temperature environment, the electrolyte can maintain good fluidity.

[0046] According to the data in Example 2, Comparative Example 5 and Table 1, when tetrafluoroborate spiro-bispyrrolidine quaternary ammonium salt is not added, the conductivity of the electrolyte at low temperature is relatively poor. However, by adding tetrafluoroborate spiro-bispyrrolidine quaternary ammonium salt, tetrafluoroborate spiro-bispyrrolidine quaternary ammonium salt has a high solubility in the solvent, which is beneficial to increase the ion concentration in the electrolyte. At a low temperature of -45°C, the electrolyte can still maintain a high conductivity, so that the capacitor can still work normally at ultra-low temperatures.

[0047] According to the data in Example 2, Comparative Example 6 and Table 1, it can be seen that the use of acetonitrile alone as a low-melting point co-solvent has limited effect on improving the low-temperature resistance of the solvent system. By introducing butylene carbonate and acetonitrile for compounding, the melting point of the mixed solvent system is effectively reduced, thereby inhibiting the crystallization of the solvent at low temperature, thereby reducing the precipitation of electrolyte salts, making the electrolyte have a higher conductivity, and improving the stability of the electrolyte at low temperatures.

[0048] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A low-temperature medium- and high-voltage aluminum electrolytic capacitor, characterized in that: It includes electrolyte, anode foil, cathode foil, lead terminal and plastic package shell; Wherein, the electrolyte comprises the following raw materials in parts by weight: 40-50 parts of main solvent, 20-30 parts of low melting point co-solvent, 15-25 parts of main solute, 5-15 parts of auxiliary solute, 5-9 parts of flash voltage enhancer, 0.7-1.3 parts of hydrogen remover, 1.2-1.8 parts of waterproofing auxiliary agent; The flash voltage enhancer is modified nano-silica, and the raw materials for preparing the modified nano-silica include polyvinyl alcohol, allyl succinic anhydride, vinyl silane coupling agent and nano-silica. The weight ratio of the polyvinyl alcohol, allyl succinic anhydride, vinyl silane coupling agent and nano-silica is (0.6-0.8): (0.3-0.5): (0.13-0.15):

1.

2. A low-temperature medium- and high-voltage aluminum electrolytic capacitor according to claim 1, characterized in that: The preparation method of the modified nano silicon dioxide is: (1) Dissolve polyvinyl alcohol in deionized water, add allyl succinic anhydride and benzoyl peroxide at 60-70°C, stir and react for 2-3 hours, add acetone after the reaction is completed to precipitate, wash and dry to obtain allyl succinic anhydride grafted polyvinyl alcohol; (2) dissolving the vinyl silane coupling agent in 95% ethanol to form a silane hydrolyzate, adding nano-silica to the silane hydrolyzate, and ultrasonically oscillating for 1-2 hours to obtain silanized nano-silica; (3) Add silanized nano-silica to deionized water, ultrasonically disperse for 30-40 minutes, add allyl succinic anhydride grafted polyvinyl alcohol, continue ultrasonically dispersing for 1-2 hours, add a mixture of benzoyl peroxide and sulfuric acid, mix evenly, stir to react for 3-4 hours, and dry to obtain modified nano-silica.

3. The low-temperature medium- and high-voltage aluminum electrolytic capacitor according to claim 1, characterized in that: The vinyl silane coupling agent is at least one of vinyl trimethoxy silane, vinyl triethoxy silane and vinyl triisopropoxy silane.

4. The low-temperature medium- and high-voltage aluminum electrolytic capacitor according to claim 1, characterized in that: The main solvent is ethylene glycol monomethyl ether.

5. The low-temperature medium- and high-voltage aluminum electrolytic capacitor according to claim 1, characterized in that: The low melting point co-solvent is prepared by compounding acetonitrile and dibutyl carbonate, and the weight ratio of the acetonitrile to dibutyl carbonate is 1:(0.5-0.9).

6. The low-temperature medium- and high-voltage aluminum electrolytic capacitor according to claim 1, characterized in that: The main solute is at least one of ammonium hydrogen phosphate, ammonium sebacate and ammonium azelate; the auxiliary solute is tetrafluoroborate spirocyclic bipyrrolidine quaternary ammonium salt.

7. The low-temperature medium- and high-voltage aluminum electrolytic capacitor according to claim 1, characterized in that: The hydrogen remover is at least one of p-nitrophenol, p-nitrobenzyl alcohol, m-nitroacetophenone and o-nitroanisole.

8. The low-temperature medium- and high-voltage aluminum electrolytic capacitor according to claim 1, characterized in that: The waterproofing auxiliary agent is at least one of phosphoric acid, hypophosphorous acid, mannitol, polypropylene alcohol, adipic acid diamide, and sorbitol.

9. The low-temperature medium- and high-voltage aluminum electrolytic capacitor according to claim 1, characterized in that: The preparation method of the electrolyte is: Heat the main solvent to 70-80°C, add the auxiliary solvent thereto, mix well and heat to 130-140°C, add the main solute and the auxiliary solute, keep warm and stir for 30-40 minutes, then cool to 110-120°C, add the flash voltage enhancer and the waterproofing auxiliary agent, keep warm and stir for 30-40 minutes, cool to 100-105°C, finally add the dehydrogenating agent, keep warm and stir for 30-40 minutes, and naturally cool to room temperature to obtain the electrolyte.

10. The low-temperature medium- and high-voltage aluminum electrolytic capacitor according to claim 1, characterized in that: The anode foil and the cathode foil are parallel to each other and are inserted into the plastic-sealed shell. The anode foil and the cathode foil are led out through lead terminals. The electrolyte is stored in the plastic-sealed shell.

Citation Information

Patent Citations

  • Low-temperature flame-retardant organic electrolyte for electric double-layer capacitor and preparation method

    CN113035586A

  • Silica lactone sol, preparation method and electrolyte for aluminum electrolytic capacitor

    CN113539689A

  • Aluminum electrolytic capacitor electrolyte, preparation method thereof and aluminum electrolytic capacitor

    CN115116751A

  • Chip electrolytic capacitor and preparation method thereof

    CN116564712A

  • Universal low-impedance electrolyte for high-voltage aluminum electrolytic capacitor and high-voltage aluminum electrolytic capacitor

    CN119340115A

Cited By

  • Acrylic acid pressure-sensitive adhesive for PE foam and preparation method of acrylic acid pressure-sensitive adhesive

    CN120924190A

  • Aluminum electrolytic capacitor electrolyte and preparation method thereof

    CN121601448A

  • Aluminum electrolytic capacitor electrolyte and method for preparing the same

    CN121601448B